Perbedaan Kecerdasan Emosi antara Siswa Kelas XI SMA Berbasis Agama dan SMA Reguler - Calista Giovani; Yusvick M Hadin; FX Bambang Sukilarso (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Emotional quotient (EQ) refers to ones ability to recognize and manage feelings, to arouse such feelings to help ones mind understand the feelings and their meanings, and to deeply control the feelings for emotional and intellectual development. Religion can improve EQ and has good influence on youth, especially high school students. Students from religion-based high school tend to have better emotional intelligence due to more religion education received, and thus its more likely application into their daily life. This aim of this research was to describe any differences of emotional quotient between 11th grade students of religion-based and regular high school. Methode: This was a descriptive analytic research with cross-sectional approach. Grade 11 students from SMA Muhammadiyah 1 Surakarta and SMA Negeri 7 Surakarta were purposively sampled based on inclusion and exclusion criteria. Subjects were asked to fill out L-MMPI scale questionnaire to measure and describe their honesty when answering questions, and EQ questionnaire. Data normality were analyzed using Kolmogorov-Smirnov test and EQ scores were compared by t-independent test using SPSS 17,0 for Windows program. Results: Analysis from 60 samples showed a significant mean difference of emotional quotient scores between level 11th grade students from the two high schools. Mean EQ scores of students from the religion-based and regular high school were 119,9 10,957 and 112,6 9,708, respectively (t = 2,719, p = 0,009). Conclusions: There was a significant difference of emotional quotient scores between 11th grade students from religion-based and regular high school. Students from religion-based high school had better emotional quotient than those from regular high school. Keywords: Emotional quotient, religion-based high school, regular high school